Вивчення впливу вмісту органічного волокна терлон на трибологічні властивості ароматичного поліаміду фенілон С-1 - Чигвінцева, Ольга Павлівна; Chigvinteva, Olha; Бойко, Юлія Володимирівна; Boiko, Yuliya (Луцький національний технічний університет, 2021)
Досліджено вплив режимів експлуатації на трибологічні властивості ароматичного поліаміду фенілон С-1 і органопластиків на його основі, армованих 15 і 25 мас. % органічного волокна терлон. Показано, що при роботі в умовах тертя без змащування низький коефіцієнт тертя та високу зносостійкість має органопластик, що містить 25 мас. % органічного волокна. Критерій працездатності вказаного органопластику більш, ніж у 2 рази вищий, ніж у полімерного в’яжучого. The influence of operating modes on the tribological properties of the aromatic polyamide phenylone C-1 and organoplastics based on it, reinforced with 15 and 25 wt. % organic fiber terlon, has been studied. It is shown that when working in conditions of friction without lubrication, the low friction coefficient and high wear resistance has the organoplastic which contains 25 wt. % organic fiber. The coefficient of friction of the specified organoplastic during operation under conditions of sliding speed  = 1 m/s in the range of specific loads P = 0.2–0.8 MPa in comparison with the initial polymer has decreased by an average of 27-63%. At sliding velocities of 1.5 and 2 m/s, the polymeric material remained operational up to maximum loads and had a friction coefficient on average 2.5 times lower than that of phenylоne C-1. Organoplastic containing 25 wt. % terlon, had minimal wear and stably worked in the entire studied mode of specific loads and sliding speeds having PV performance criterion more than 2 times higher than that of the polymeric binder.
Study of the influence of terlon organic fiber content on tribological properties of aromatic polyamida phenilon с-1
Keywords: ароматичний поліамід фенілон С-1; aromatic polyamide phenylone, organic fiber terlon; органічне волокно терлон; organic fiber terlon; органопластики; organoplastics; трибологічні властивості; tribological properties; коефіцієнт тертя; friction coefficient; інтенсивність лінійного зношування; intensity of linear wear; критерій працездатності; performance criterion